Serum Uric Acid Increases Risk of Cancer Incidence and Mortality: A Systematic Review and Meta-Analysis - Shushan Yan; Pengjun Zhang; Wei Xu; Yuqing Liu; Bin Wang; Tao Jiang; Changjiang Hua; Xuan Wang; Donghua Xu; Beicheng Sun (Hindawi Limited, 2015)
SUA is a potent antioxidant and thus may play a protective role against cancer. Many epidemiological studies have investigated this hypothesis but provided inconsistent and inconclusive findings. We aimed to precisely elucidate the association between SUA levels and cancer by pooling all available publications. Totally, 5 independent studies with 456,053 subjects and 12 with 632,472 subjects were identified after a comprehensive literature screening from PubMed, Embase, and Web of Science. The pooled RRs showed that individuals with high SUA levels were at an increased risk of total cancer incidence (RR=1.03, 95% CI 1.01-1.05, P=0.007). Positive association between high SUA levels and total cancer incidence was observed in males but not females (for men: RR=1.05, 95% CI 1.02-1.08, P=0.002; for women, RR=1.01, 95% CI 0.98-1.04, P=0.512). Besides, high SUA levels were associated with an elevated risk of total cancer mortality (RR=1.17, 95% CI 1.04-1.32, P=0.010), particularly in females (RR=1.25, 95% CI 1.07-1.45, P=0.004). The study suggests that high SUA levels increase the risk of total cancer incidence and mortality. The data do not support the hypothesis of a protective role of SUA in cancer.